Nationwide multi-centric prospective study for the identification of biomarkers to predict the treatment responses of nivolumab through comprehensive analyses of pretreatment plasma exosome mRNAs from head and neck cancer patients (BIONEXT study) - Sato, Kuniaki; Toh, Satoshi; Murakami, Taku; Nakano, Takafumi; Hongo, Takahiro; Matsuo, Mioko; Hashimoto, Kazuki; Sugasawa, Masashi; Yamazaki, Keisuke; Ueki, Yushi; Nakashima, Torahiko; Uryu, Hideoki; et al. (Frontiers in Immunology, 2025)
BackgroundNivolumab paved a new way in the treatment of patients with recurrent or metastatic (RM) head and neck squamous cell carcinoma (RM-HNSCC). However, the limited rates of long-term survivors (< 20%) demand a robust prognostic biomarker. This nationwide multi-centric prospective study aimed to identify a plasma exosome (PEX) mRNA signature, which serves as a companion diagnostic of nivolumab and provides a biological clue to develop effective therapies for a majority of non-survivors.MethodsPre-treatment plasmas (N = 104) of RM-HNSCC patients were subjected to comprehensive PEX mRNA analyses for prognostic marker discovery and validation. In parallel, paired treatment-naïve tumor and plasma samples (N = 20) were assayed to elucidate biological implications of the PEX mRNA signature.ResultsAssays for pre-treatment blood samples (N = 104) demonstrated that a combination of 6 candidate PEX mRNAs plus neutrophil-to-lymphocyte ratio precisely distinguished non-survivors from >2-year survivors (2-year OS; 0% vs 57.7%; P = 0.000124) with a high hazard ratio of 2.878 (95% CI 1.639-5.055; P = 0.0002348). Parallel biological assays demonstrated that in the paired treatment-naïve HNSCC tumor and plasma samples (N = 20), PEX HLA-E mRNA (a non-survivor-predicting marker) was positively corelated with overexpression of HLA-E protein (P = 0.0191) and the dense population of tumor-infiltrating NK cells (P = 0.024) in the corresponding tumor, suggesting that the HLA-E-NKG2A immune checkpoint may inhibit the antitumor effect of PD-1blockade.ConclusionThe PEX mRNA signature could be useful as a companion diagnostic of nivolumab. The combination of an anti-NKG2A antibody (i.e., monalizumab) and nivolumab may serve as a treatment option for non-survivors predicted by a RT-qPCR-based pre-treatment measurement of PEX mRNAs.